EVALUATION OF THE CLINICAL SAFETY OF ORAL CURCUMIN TREATMENT IN NILE TILAPIA (Oreochromis niloticus) - ARAUJO, K. S.; KLINGER, B. A. R.; PULTZ, M. E.; CARLINO-COSTA , C.; VIEIRA, E. C.; RODRIGUES, L. F.; ARACATI, M. F.; OLIVEIRA, S. L.; BELO, M. A. A. (Ars Veterinaria, 2024)
Curcumin is considered a multifunctional feed additive, with immunostimulant properties. Given this potential, it is crucial to deepen studies on the safety of substances like curcumin in fish, ensuring its safe and effective use for sustainable aquaculture. In this context, the present study aimed to evaluate the clinical safety of curcumin in tilapia, administered orally via feed, through hematological and biochemical analyses. A total of 63 fish (±100g) from a commercial fish farm, Sales de Oliveira/SP, were randomly distributed in 9 tanks of 100 L each, supplied with chlorine-free water. The treatments were: T0 (control, without curcumin), T1 and T2 (treated with 100 and 400 mg/kg of curcumin, respectively). Seven fish were sampled per treatment at four time points: 4, 8, and 12 days post-treatment (DPT), along with an additional recovery period up to day 16. Blood samples were collected for hematological and biochemical analysis, along with somatic evaluation of the organs. The results showed a significant increase in the number of erythrocytes and hematocrit in tilapia treated with curcumin, particularly at doses of 400 mg/kg at 12DPT and 100 mg/kg at 16DPT. There were no significant differences in the leukogram, total protein levels, or somatic index of the organs between the groups. Serum creatinine levels temporarily decreased, returning to baseline levels, and a significant peak in glucose levels was observed at 16DPT, especially at the 400 mg/kg dose. Further studies are needed to elucidate the mechanisms involved and confirm the clinical safety of curcumin over longer periods.